PERSELISIHAN HAK ATAS UPAH PEKERJA TERKAIT UPAH MINIMUM KABUPATEN/KOTA (UMK) - Kesuma, I Nyoman Jaya (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2017)
Salary are basic rights for workers. For the sake welfare of workers, be established regulations by government related to minimum salary of workers every year has changed adjust the economy in Indonesia. Violations of right against minimum salary of worker can happen so The problem related to protection of workers rights related to Minimum Salary in District / City and legal action for workers related rights disputes to workers salary below the minimum salary in District / City. In the discussion on the right to worker salary related to minimum salary workers protected by law by the act and the implementing regulations and legal action that can be taken by workers in case of rights violations salary may take legal action out of court until the legal action through the courts for the rights of workers.